Pengelolaan Zakat Produktif Ternak Kambing Dalam Perspektif Hukum Islam - Zul Fahmi; Muh. Nashirudin (LPPM ISNJ Bengkalis, 2022)
This research was conducted to analyze how the productive zakat program for goats was carried out by Baitul Mal Forum Komunikasi Antar Masjid (BMFKAM) Surakarta and how Islamic law reviewed the implementation of the program. This study uses a qualitative method with a normative juridical approach. Interviews and documentation carried out data collection techniques. The results of the study found that there was compatibility between the productive zakat program for goat livestock implemented by BMFKAM Surakarta with Islamic law and laws regarding zakat management. The productive zakat program for goats has a tremendous economic impact on beneficiaries, including jobs and opportunities to improve their welfare. Theoretically, this research can be an additional reference for other researchers and academics who wish to conduct the same research on productive zakat, especially goats. This research can inspire the community and zakat managers to make zakat distribution programs more creative, innovative, and beneficial for the community's economic development.